Basic Concepts Of IntegralDifferential Equations - Nafasov Ganisher Abdurashidovich; Eshkuvatov Kozim; Eshmuratov Abdimannab (Genius Journals, 2025)
This article analyzes the essence of integro-differential equations, their role in mathematical modeling, and their significance for describing physical, technical, and biological processes. Integro-differential equations represent a class of complex equations that combine differential and integral operations. The article discusses their main types, solution methods, and the advantages of analytical and numerical approaches. The influence of the integral kernel and boundary conditions on the equation's solution is also theoretically substantiated
Keywords: integrodifferential equation; integral kernel; analytical solution